Estudos de longevidade e germinação em sementes de espécies do gênero Melocactus (Cactaceae) de Morro do Chapéu, Chapada Diamantina, Bahia - Cruz, Brisa Mascarenhas (2011)
The genus Melocactus (Cactaceae) has 37 species, of these 11 are endemic to Bahia. As an alternative to conservation of this genus, studies are needed regarding the behavior of these species, whereas nine species are endangered. Seed storage is a method of conservation which aims to preserve the physical and physiological quality of seeds. The objective of this study was to evaluate the best storage condition for up to 24 months of the seeds of M. ernestii, M. glaucescens and M. xalbicephalus. For this purpose, seeds were exposed to different conditions: refrigerator and room temperature, presence and absence of silica and paper packaging in impermeable containers of glass. For analysis of seed germination, seeds were sterilized in 2.5% NaOCl for 10 minutes and washed three times in distilled water. These were sown in Petri dishes containing germitest paper and maintained in a growth chamber at 25 ± 3 ° C and a photoperiod of 16 hours. We used an entirely randomized design with four repetitions of 25 seeds and germination assessments were daily for 21 days after sowing considering as germinated the radicle emission. We assessed the relative frequency of germination, germinability, germination speed rate, average time of germination and germination uniformity coefficient. We also examined the content of the seed humidity and as for conditioning the seed feasibility was evaluated by tetrazolium test in the control and after 6 months of storage. After 24 months the seeds of M. ernestii remained feasible when placed at room temperature in the absence of silica and refrigerator in the presence of silica. For storage of M. ernestii, M. glaucescens and M. xalbicephalus for up to six months the conditioning in room temperature in the presence of silica showed the best results.